Fluid characheristics of the Baoxingchang Cu-Mo Deposit, Yunnan Province, SW China. Issue 2 (January 2021) - Dao, Yan; Jian, Long; Xiao, Gaoqiang; Zhang, Yourong; Xu, Shengchao
Abstract: The Baoxingchang Cu-Mo deposit is an important deposit in the Jinshajiang-Red River alkali-rich porphyry area, Western Yunnan. Fluid inclusion petrography and inclusion microscopic thermometric analysis of quartz phenocrysts in non-mineralized porphyritic granite, lamprophyre quartz veins, molybdenite quartz veins, copper-pyrite-molybdenite quartz veins, and pyrite quartz veins show that the development in primary inclusion of quartz phenocrysts and quartz veins can include vapour-rich inclusions and liquid-rich inclusions. Fluid inclusions are characterised by their medium-high temperature and moderate salinity. However, the temperature and salinity of non-mineralised quartz fluid inclusions are higher than those of quartz fluid inclusions in the mineralisation stage. Captured pressure and mineralisation depth during mineralisation reveal that the copper-molybdenum deposit is formed in hypabyssal environment, which is consistent with porphyry metalloginic systems.